GOLF PROMOTION DESIGN OF GOLF WIRABRAJA PURI GARDENA ULU GADUT THROUGH MEDIA WEBSITE - MONICA NOVITA PUTRI, Drs. Syafwan, M.Si., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Golf Course Wirabraja Castle Gardena is located at Jl.Raya Ulu Gadut No.8 Lubuk Kilangan, Padang City, West Sumatera 25157. The purpose of designing this website as a media promotion of Golf Course Wirabraja Castle Gardena to provide information directly and visualization about the Golf Course Wirabraja Puri Gardena. In order to attract the heart and facilitate the visitors, to play or exercise golf and can affect the target audience and market segmentation because the majority of people now more access the internet in everyday life.The design of this website is done through several stages of data collection, data analysis and design. The process of collecting data through interviews with the manager and the cady at the Golf Course Wirabraja Castle Gardena. While the process of data analysis by 5W + 1H, obtained through the collection of data observation and documentation directly to the Golf Course Wirabraja Castle Gardena. This website design is tailored for mobile phone, featuring 5 serving menu, namely: home, golf, tournaments, gallery, contact us.Keywords: Golf Course Wirabraja Castle Gardena, Website,Mobile phone, Internet.